ANALISIS PROSES MORFOLOGIS PADA ARTIKEL TAJUK RENCANA KORAN HARIAN WASPADA - Andi Syahputra Harahap, Muyassarah, Susy Deliani (Linguistik : Jurnal Bahasa dan Sastra, 2024)
The purpose of this research is to describe the morphological process of affixation and reduplication used by the writer in the editorial articles of Waspada Daily Newspaper. The research method used in this research is descriptive qualitative. Data collection is in the form of observation and documentation methods, then reading and recording parts of the article Tajuk Rencana Koran Harian Waspada which includes a discussion of the morphological process of affixation and reduplication. The reading technique is done by reading the editorial articles of the Waspada Daily Newspaper to find the object of research. The note-taking technique is done so that after reading things that include can be reviewed again. The subject that becomes the focus of this research is the editorial articles of Waspada Daily Newspaper. The object of the research is the morphological process of affixation and reduplication in the editorial articles of Waspada Daily Newspaper. The subject of the research is the editorial articles of Waspada Daily Newspaper. The important data will be the subject of this research is marked and recorded to be grouped according to the morphological process of affixation and reduplication that will be studied. The results of this study found that the morphological processes of affixation and reduplication contained in the editorial articles of the Waspada Daily Newspaper include: first, the morphological process of affixation has five types, namely the prefixation process of 713 words, the infixation process of 0 words, the suffixation process of 280 words, the confixation process of 115 words, and the simulfixation process of 552 words. Secondly, the morphological process of reduplication has four types, namely the repetition process with all words 75 words, the repetition process of some words 21 words, the repetition process with morpheme changes 12 words, and the repetition process with affixation 16 words.